2020
DOI: 10.9734/ajahr/2020/v6i230069
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield and Biochemical Characteristics of Tomato (Solanum lycopersicum L.) Genotypes under Seasonal Heat Stress

Abstract: This field study was conducted to evaluate yield and fruit quality of tomato genotypes under seasonal heat stress condition (April-June) in plains of Chitwan valley, Nepal for two consecutive years in 2018 and 2019 at research farm, of Agriculture and Forestry University, Rampur, Nepal. Nine tomato genotypes were evaluated for their morphological, flowering, yield and biochemical traits in a randomized complete block design with four replications. Results showed significant differences (P = 0.05) among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Chapagain et al (2020a) studied in tomatoes for fruit yield and yield contributing traits and were grouped into one cluster having taller plants with higher marketable fruits per plant, fruit set percentage, flowers per inflorescence, marketable fruits and fruit yield per plant. Tomato genotypes with semi-determinate to indeterminate growth habit with medium sized fruits performed better in yield and quality attributes (Chapagain et al, 2020b). It has been reported that the highest marketable fruit yield of 34.0 and 32.0 mt ha -1 was recorded in genotype AVTO9802 in 2018 and 2019, respectively with the mean yield of 32.9 mt ha -1 .…”
Section: Correlation Analysismentioning
confidence: 95%
“…Chapagain et al (2020a) studied in tomatoes for fruit yield and yield contributing traits and were grouped into one cluster having taller plants with higher marketable fruits per plant, fruit set percentage, flowers per inflorescence, marketable fruits and fruit yield per plant. Tomato genotypes with semi-determinate to indeterminate growth habit with medium sized fruits performed better in yield and quality attributes (Chapagain et al, 2020b). It has been reported that the highest marketable fruit yield of 34.0 and 32.0 mt ha -1 was recorded in genotype AVTO9802 in 2018 and 2019, respectively with the mean yield of 32.9 mt ha -1 .…”
Section: Correlation Analysismentioning
confidence: 95%